Creating High‐Impact Literature Reviews: An Argument for ‘Integrative Reviews’ - Elsbach, Kimberly D.; van Knippenberg, Daan (Journal of Management Studies, 2020)
AbstractIn this article, we argue that integrative literature reviews are among the most useful vehicles for advancing knowledge and furthering research in a topic domain. Integrative literature reviews are strongly anchored in a representative description of a field, but add new insights via a critical analysis and synthesis of the field’s literature. Based on this definition, we explicate the ways that scholars can (1) define the ‘space’ for an integrative review (i.e., how they can justify and bound an integrative review), and (2) synthesize insights gained from the review to develop a new perspective or point of view on the literature. We illustrate these points with several of the most highly‐cited manuscripts published in the Academy of Management Annals. Finally, we close by arguing why these points make integrative reviews most useful for advancing knowledge and furthering research in the area of management.